New nuances of motherhood: the search for a new equilibrium - Santos, Natália De Toni; Zornig, Silvia Maria Abu-jamra (Analytica: Revista de Psicanálise, 2021)
The concept of primary maternal preoccupation, introduced by Donald Winnicott in the 1960’s, refers to a state of profound attunement between the mother and the infant during the first months of the baby’s life, implying in the temporary retrieval of her personal investments to be able to deeply identify herself to the emotional needs of her baby. Our question in this article then consists in how, in the present socio-cultural context, especially in the middle classes, the establishment of this delicate maternal state occurs. We observed that the increase in social demands on women, principally in relation to professional investments, compared to what we had at the time the concept was created, has repercussions on the maternal experience, adding new nuances to the state of primary maternal preoccupation.